Stabilization of impulsive switched linear systems with saturated control input - Chen, Yonggang; Fei, Shumin; Zhang, Kanjian (Nonlinear dynamics, 2012)
This paper considers the stabilization problem of impulsive switched linear systems with saturated control input, in which the impulses are viewed as control or disturbances. Under arbitrary switching rule and dwell time switching rule, the local stabilization conditions are obtained in terms of LMIs, respectively. The corresponding optimization problems are formulated to obtain a bigger attractive region. Our results show that impulsive control can recover part of attractive region, or allow a wide range of switching signals. If the impulses occur as disturbances, we have to increase the dwell time of switching signals to offset the effects of disturbances. Numerical examples are given to show the effectiveness of the results proposed.